Development of porous Ti-6Al-4V mix with palm stearin binder by metal injection molding technique - Jamaludin, Mohamad Ikhwan; Abu Kasim, Nur Atikah; Mohamad Nor, Nor Hafiez; Ismail, Muhammad Hussain (Science Publications, 2015)
Good potential of biocompatibility and excellent mechanical properties, porous Ti-6Al-4V has become a great interest for biomedical applications. In this study, porous Ti-6Al-4V was fabricated by Metal Injection Molding (MIM) using Palm Stearin (PS) and Polyethylene (PE) binder together with sodium chloride (NaCl) as a space holder. Rheological characterization was performed to evaluate the flowability of the feedstocks for injection molding and the feedstocks exhibited a pseudoplastic behavior which is suitable for injection. The as-sintered parts were fabricated as the mixing, injection molding, debinding and sintering were conducted successfully. The mechanical properties of the as-sintered parts were investigated via tensile test and the results obtained were closed with the established range. Shrinkage, density and X-Ray Diffractometry (XRD) of the as-sintered parts were compared with the theoretical values which were found closed to the acceptable ranges. The microstructure of the surface and cross-section were observed under Scanning Electron Micrograph (SEM) and optical microscope to analyze the specimens before and after sintering. Generally, palm stearin binder system added with space holder to fabricate porous Ti-6Al-4V by MIM is feasible and has shown a good potential for biomedical applications.